2024
DOI: 10.1021/acs.orglett.4c01201
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Regio- and Enantioselective N-Allylation of Pyrazoles with Dienyl/Monoallylic Alcohols

Peng Zhang,
Yulu Zhang,
Ying Shao
et al.

Abstract: Here we report the first example of iridium-catalyzed asymmetric N-allylation of pyrazoles with dienyl allylic alcohols under mild conditions with broad functional group tolerance, exhibiting excellent N 1 /C3site selectivities and enantioselectivities (up to >99% ee). In addition to pyrazoles, other nucleophiles including benzotriazole, triazole, and pyrazole precursors (aryl vinyldiazos) are also suitable in this method. Notably, with the use of Sc(OTf) 3 as additive and reactions performed at 30 °C for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…On the basis of the previous literature, , control experiments (for detailed information, see the Supporting Information, page s32), and our own results, a mechanism for this protocol is proposed in Scheme a. First, rhodium(I) species A , produced from [Rh(cod)Cl] 2 with ( S )- L , followed in the presence of HCO 2 H, undergoes oxidative addition with dienyl alcohol 1a to generate the (η 3 -allyl)rhodium(III) species Int A and its tautomer Int B through a process of π–σ–π transformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the previous literature, , control experiments (for detailed information, see the Supporting Information, page s32), and our own results, a mechanism for this protocol is proposed in Scheme a. First, rhodium(I) species A , produced from [Rh(cod)Cl] 2 with ( S )- L , followed in the presence of HCO 2 H, undergoes oxidative addition with dienyl alcohol 1a to generate the (η 3 -allyl)rhodium(III) species Int A and its tautomer Int B through a process of π–σ–π transformation.…”
mentioning
confidence: 99%
“…Traditionally, transition-metal-catalyzed asymmetric allylic substitution (AAS) reactions of 1,4-dienyl allylic precursors have been dominated by palladium and iridium catalytic systems, and mixed products are usually obtained because of the nucleophilic competitive attack at the C1/C3/C5 position of the 3-vinyl-1-π-allyl metal complex intermediate Int-A (Scheme , a-1). , Recently, great developments have been made in regioselective allylic substitution of dienyl allylic substrates . For example, the C3-product could be achieved in a high regio- and enantioselective manner. The C1-product also has been synthesized in controllable ways. , However, C5-regio- and enantioselective allylic amination of dienyl substrates remains a big challenge; the reason may be attributed to the fact that Int B is more difficult to be formed than Int A (Scheme , a-1) . For instance, the previous works of Hou et al, Gong et al, and our group ,, have all revealed that C5-selective amination proceeds through a mechanism of C5–S N 2′ of Int A , which results in racemic products (Scheme , a-1 and b).…”
mentioning
confidence: 99%